Ghost Dances on Silver Screens: Pumzi and Older Than America. Issue 1 (2016) - Hairston, Andrea
Abstract : "Ghost Dances on Silver Screens: Pumzi and Older Than America " is a meditation on the ghost artistry of filmmakers Wanuri Kahiu and Georgina Lightning. Ghosts are an embodiment of the invisible forces of a past that hasn't gone anywhere. Revealing what is normally concealed, ghosts are sacred/demonic tricksters who provide alternate perspectives on the here and now and on the future. Asha from Kahiu's Pumzi and Rain from Lightning's Older than America engage with the ghosts of their ancestors not as an exercise in nostalgia for a paradise lost nor as a scare-you-to-death adrenaline ride. Rain and Asha dance with the ancestors so that they might reorder the cosmos. They are futurists, reanimating and reinventing the world.